An ultrasensitive label-free immunoassay for C-reactive protein detection in human serum based on electron transfer. Issue 32 (27th July 2016) - Zhang, Xi; Hu, Rong; Zhang, Kunlei; Bai, Ruyan; Li, Delei; Yang, Yunhui
Abstract : A rapid, ultrasensitive, and practical label-free electrochemical immunoassay for measuring C-reactive protein (CRP) in real serum samples was developed. Abstract : A rapid, ultrasensitive, and practical label-free electrochemical immunoassay for measuring C-reactive protein (CRP) in real serum samples was developed. Molybdenum disulfide–polyaniline–gold nanoparticles (MoS2 –PANI–GNPs) with high conductivity were employed as the substrate to assist the electron transfer. Compared with a bare electrode, an about 10-fold increase in the peak current could be detected for MoS2 –PANI–GNPs. Moreover, MoS2 –PANI–GNPs which have abundant adsorbing sites and a large surface area could greatly increase loading amounts of antibodies and thus, significantly improve the performance of biosensing. Under optimized experimental conditions, the proposed sensing strategy provides a linear dynamic range from 0.2 to 80 ng mL −1 and a detection limit of 40 pg mL −1 . The proposed immunosensor has also been used to determine CRP in human serum with satisfactory results. This possibly makes it an attractive platform in bioanalysis of proteins and other molecules.